Forest land use by the community in Sorong Natural Tourism Park at Sorong City, West Papua Province - YOHANES YOSEPH RAHAWARIN (Biodiversitas Journal of Biological Diversity, 2010)
Rahawarin Y (2011) Forest land use by the community in Sorong Natural Tourism Park at Sorong City, West Papua Province. Biodiversitas 12: 222-227. The aim of the research was to: (i) identify the type and extent of forest land use alteration at Sorong Natural Tourism Park (or SNTP), (ii) investigate society activities that cause forest land use alteration, and (iii) make the zoning level of environmental damage (iv) investigate the causative factors of forest land use alteration at SNTP. The method used was survey with field observation and semi-structural interview techniques. The primary data of biophysical aspects consist of type and extents of land usage by society; while data of socio-cultural aspects consist of level of community dependency upon land and the existing of local institution and management of SNTP. Secondary data that had been collected consist of study results documentation and report of SNTP management aspects. Data were analyzed by using (i) qualitative descriptive analysis of society socio-cultural and management aspects, (ii) spatial analysis of biophysical aspects, and (iii) environmental analysis of biophysical, socio-cultural and management aspects.Evaluation of environmental analysis was used to arrange directive and environmental management strategy at SNTP. Result of research indicated that since its establishment in 1981 to 2009, SNTP forest land utilizing for settlements, forest product extraction and shifting cultivation activity by society had been cause of land use alteration occurred which was incompatible with area function about 11,53%. Changing in the land use caused by society activities in land utilizes such settlements, forest product extraction and shifting cultivation.Level of environmental degradation in the catchments area of damage SNTP level indicates that 8.01% of total of land area was in slightly damaged, 2.36% was moderately damaged and 1.16% is in heavily damaged. Inadequate support on socio-cultural aspects of society at SNTP and the lack of founding and supervising upon SNTP management was pointed as causative factors on environmental damage. Based on level of environmental damage, community based forest management system will be able to be implemented as environmental management strategy at SNTP.Key words: forest land use, environmental degradation, Sorong Natural Tourism Park